AMERICAN RACE RELATIONS: SOCIOLOGY 3211 W - Hartmann, Douglas (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
"The problem of the 20th century," W.E.B. DuBois wrote over 100 years ago, "is theproblem of the color line." Still today in the 21 st century, a good deal of evidence would seem to vindicate DuBois's bold prediction. But if most Americans can agree that race is a problem in the U.S., there is a tremendous amount of disagreement about almost everything else having to do with race. Why has race been so problematic? Who (or what) is to blame? Have the problems posed by race changed in recent years? Will race continue to be a problem in the 21 st century? If so, what should we do about it? What can we do about it? Can anything positive come of all this? This course is designed to help students begin to develop their own informed perspectives on American racial "problems" by introducing them to the ways that sociologists deal with race, ethnicity, race relations and racism.